Cane Hay Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_2003_10
Keywords: MF997; Economics; Crops; MF